Ultrastructure of the parotid and submandibular glands of the Old World marten (Carnivora; Mustelidae) - Junior, B. K.; Masuko, T. S. (Gustav Fischer Verlag, 1998)
The morphology of the parotid and submandibular glands in the marten, a carnivore, were studied and analyzed under a transmission electron microscope. The nature of the granules in both glands, as well as in the acini and in the secretory tubules, is rather mucous. The structure of the secretory tubules is very characteristic, especially the striated ones. The myoepithelial cells are close to the acini and tubules and covered by the basement membrane separating them from the connective tissue, which enhances its epithelial origin. The cytoplasm of the basal parts of the acinar and tubular cells is abundant and separates the nucleus from the secretion granules. Although the morphology of the salivary glands of many carnivores is known, those of the parotid gland of the marten present peculiar characteristics, since they produce a rather mucous saliva and the granules, when forming, are far from the base as well as from the apex of the secretory cells. The submandibular gland contains granules of different densities, an aspect that in general resembles that of other animals.
Keywords: salivary glands; parotid gland; submandibular gland; carnivore; transmission electronmicroscopy; ultrastructure